2012
DOI: 10.1155/2012/754186
|View full text |Cite
|
Sign up to set email alerts
|

Posture and Locomotion Coupling: A Target for Rehabilitation Interventions in Persons with Parkinson's Disease

Abstract: Disorders of posture, balance, and gait are debilitating motor manifestations of advancing Parkinson's disease requiring rehabilitation intervention. These problems often reflect difficulties with coupling or sequencing posture and locomotion during complex whole body movements linked with falls. Considerable progress has been made with demonstrating the effectiveness of exercise interventions for individuals with Parkinson's disease. However, gaps remain in the evidence base for specific interventions and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…We anticipated that stimulation of the lateral malleolus of the initial stance limb would reinforce the APA sequence in a manner similar to studies that provided postural assistance via sural nerve stimulation, 26 floor vibration, or a support surface drop of the stance limb. 27,28 Our findings illustrate the challenges of using a cutaneous or proprioceptive sensory cue in a population that often has compromised sensation due to ageing, parkinsonism and additional neurological complications. 29,30 Though impairments in vision and hearing can also reduce effectiveness of external cueing, all modalities showed improvement relative to self-initiated stepping.…”
Section: Discussionmentioning
confidence: 70%
“…We anticipated that stimulation of the lateral malleolus of the initial stance limb would reinforce the APA sequence in a manner similar to studies that provided postural assistance via sural nerve stimulation, 26 floor vibration, or a support surface drop of the stance limb. 27,28 Our findings illustrate the challenges of using a cutaneous or proprioceptive sensory cue in a population that often has compromised sensation due to ageing, parkinsonism and additional neurological complications. 29,30 Though impairments in vision and hearing can also reduce effectiveness of external cueing, all modalities showed improvement relative to self-initiated stepping.…”
Section: Discussionmentioning
confidence: 70%
“…23,30 Furthermore, the findings of increased variability in neuromechanical force modulation during the preparation phase but not while stepping also suggested that the identification of APA impairments at an earlier stage of PD, may be helpful to developing rehabilitation interventions directed at minimizing or slowing the progression of further stepping abnormalities during gait initiation. 18 …”
Section: Discussionmentioning
confidence: 99%
“…18 In this scheme, a step will be initiated when sufficient anticipated postural state conditions for balance stability related to the relationship between the CoM and BOS are achieved by APAs generating the weight transfer from bipedal to single limb support. 18 Using this framework, both acute and immediate improvements in gait initiation have been observed with the application of external mechanical or sensory stimuli applied early in the postural adjustment phase that assists the APAs by facilitating weight transfer and achieving a more stable anticipated postural condition prior to the initiation release of stepping. 12,14,16 It remains to be determined, however, whether the variability of APA parameters during gait initiation may also be improved through external postural enhancement to modify posture-locomotion coupling with practice training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing research is being conducted to correlate thresholds to isometric strength for older adult women. Previous research, however, suggests that thresholds and isometric strength will not be strongly correlated [32]. …”
Section: Discussionmentioning
confidence: 99%